At Risk of "Leftover Singles": Dimensions and Sociopsychological Repercussions of Delayed Marriageability Among Educated Females in Pakistan. (October 2020) - Sultan, Tipu; Ahmad, Saeed; Ayub, Ayesha
The current study examined the educational, economic, and sociocultural, family and personal dimensions of delayed marriage among educated females in Pakistan. In addition, it revealed family-based and personal dimensions of delayed marriage among educated females in Pakistan. Furthermore, it highlighted the sociopsychological consequences of delayed marriageability among females in patriarchal society. For this purpose, 35 females, in the age bracket of 30–49 years and with a minimum of 16 years of education, were recruited for the current study through purposive and snowball sampling technique. An interview guide was used as a tool for data collection. The main sociocultural factors of delayed marriageability were the unavailability of a suitable match in the marriage market, the provision of the dowry, the pivotal role of the caste system and the second fiddle role of sectarian affiliation, and previous marital status (engaged or divorced) of the females. The structure and the size of the family were also the decisive family factors of delayed marriageability. Additionally, among personal traits, physical outlook and effective individualism played a prominent role. The current study conjectured a relational insight and transformation in a family structure for family demographers. It was the first qualitative study to highlight the patriarchal perspective of Pakistani society on the factors of delayed marriages. The findings of the current study would enrich the overall theoretical understanding of delayed marriageability among females.